Immune checkpoint proteins are associated with persistently high liver stiffness after successful HCV treatment in people with HIV: a retrospective study - Martín-Escolano, Rubén; Virseda-Berdices, Ana; Berenguer, Juan; González-García, Juan; Brochado-Kith, Oscar; Fernández-Rodríguez, Amanda; Díez, Cristina; Hontañon, Victor; Resino, Salvador; Jiménez-Sousa, María Ángeles (Frontiers in Immunology, 2024)
Various immune checkpoint proteins have been linked to cirrhosis. This study aimed to explore the association between plasma levels of these proteins measured one year after successful HCV treatment and persistently liver stiffness (defined as liver stiffness measurement (LSM) ≥ 12.5 kPa) five years after HCV treatment in people with HIV (PWH). We conducted a retrospective study involving 39 patients with HIV/HCV-coinfection who had advanced fibrosis or cirrhosis and achieved sustained virologic response (SVR). Plasma samples were obtained one year after treatment, and levels of immune checkpoints along with inflammatory biomarkers were evaluated using a Luminex 200TM analyzer. Statistical analyses were performed using Generalized Linear Models (GLMs) with a gamma distribution. Spearman correlation tests were used to analyze the correlation between significant immune checkpoints and inflammatory biomarkers. Although LSM values showed a decreasing trend over the years following successful HCV treatment, this trend was not statistically significant due to substantial variability among PWH. Persistently high liver stiffness was observed in 61.5% of patients five years after HCV treatment. Elevated plasma levels of soluble BTLA, PD-1, and TIM-3 one year after HCV treatment were associated with persistently liver stiffness five years later. These significant immune checkpoints were found to correlate with inflammatory biomarkers in PWH with persistently high liver stiffness. In conclusion, increased plasma concentrations of immune checkpoints one year after successful HCV therapy were linked to persistently high liver stiffness five years later, particularly BTLA, PD-1, and TIM-3. This suggests a potential immunopathological mechanism in ongoing liver stiffness post-HCV eradication.